Effects of Mindfulness-Based Cognitive Therapy on Attributional Styles of Students - F. Hamidi, Ph.D.; H. Jalilian (خانواده و پژوهش, 2019)
The purpose of this study was to investigate the effects of mindfulness-based cognitive therapy on attributional styles and learned helplessness of students. This quasi-experimental research had a pretest-posttest control group design. The statistical population of the study comprised all eleventh grade female students in Maryam high school in Khorramshahr enrolled in academic year 2015-2016. The sample consisted of 30 female students who were selected through simple random sampling method and assigned to experimental and control groups (15 students in each group). The instrument included Seligman Attributional Style Questionnaire (1984). The experimental group received mindfulness-based cognitive therapy in 8 ninety-minute sessions. The obtained data were analyzed via descriptive (mean, standard deviation, and variance) and inferential statistics (ANCONA). The results showed that mindfulness-based cognitive therapy was effective in reducing students’ learned helplessness and it increased attributional styles for positive and negative events in the experimental group compared to the control group (p≤0.05). This intervention has positive impacts on students’ cognitive and information processing systems and boosts their performance through increasing individuals’ focused awareness on the present moment. Hence, it is suggested that workshops and in-service training courses be held in schools and counseling centers to familiarize teachers and counselors with mindfulness-based cognitive therapy.